Management of Rangeland Livestock under Drought - Horn, Blaine E; Hart, Charles R; Paisley, Steven I (Annals of Arid Zone, 2016)
Below "normal" precIpitation often results in severe drought in arid and semi-arid regions with a reduction in forage for livestock and wildlife. However, the amount of forage produced in any year is dependent upon the amount and timing of precipitation. Plants subjected to overgrazing during severe drought can loose vigor, resulting in loss of cover. Minimizing the negative effects of drought on the range resource, as well as financially surviving the drought are management objectives for range livestock producers. Adherence to the principles of rangeland management prior to, during, and after a drought is crucial in maintaining rangeland productivity. Understanding forage supply and livestock forage demand, in addition to livestock nutrient needs is important in maintaining range condition and livestock health, Stocking rate reductions and weaning practices should proceed in a planned, systematic manner to minimize range degradation and maximize financial returns. Management practices, such as supplemental or substitute feeding should be based on economics. Alternative feed sources may provide emergency rations that are economical. Because droughts are inevitable, especially in arid and semi-arid regions, planning for them by livestock producers, rangeland managers and government policy makers is crucial. Drought plans should include guidelines for stoGking rate reductions. Government drought management policies should encourage grazing and land management practices that minimize negative effects of drought. Policies that assist in purchase of harvested feeds are not recommended if they lead to rangeland degradation by delaying destocking.